2018
DOI: 10.22159/ajpcr.2018.v11i3.23522
|View full text |Cite
|
Sign up to set email alerts
|

Berries Supplementation Modulates Body Weight and Metabolic Deteriorations in Obese Rats

Abstract: Objective:The aim of the present work is to investigate the potential of purple (Morus rubra [MR]) and white (Morus alba [MA]) berry supplementation to modulate body weight (BW) and metabolic deteriorations in obese Wistar male rats.Methods: Seventy rats weighing 150.00±10 g (mean±standard deviation) were used; the rats were randomly divided into seven groups of 10 rats each. Obesity was induced by feeding animals high-fat diet (HFD), for 6 consecutive weeks then treated with the purple (MR) and white (MA) ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The potential effects of compounds related to these classes in reducing cerebral injury and improving cognitive function were reported [1,2,6]. Morus species has been approved as effective against metabolic deteriorations and Al-induced developmental retinopathy [5,9]. None of these studies have demonstrated the effect of M. rubra and M. alba against Al-neurotoxicity at biochemical and electron microscopic levels.…”
Section: El-baz Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…The potential effects of compounds related to these classes in reducing cerebral injury and improving cognitive function were reported [1,2,6]. Morus species has been approved as effective against metabolic deteriorations and Al-induced developmental retinopathy [5,9]. None of these studies have demonstrated the effect of M. rubra and M. alba against Al-neurotoxicity at biochemical and electron microscopic levels.…”
Section: El-baz Et Almentioning
confidence: 99%
“…Neurodegenerative diseases are related to deficiency of antioxidants that could be prevented by radical scavengers [7,8]. Morus genus, a member of the Moraceae family, is a fruit that has a high content of radical scavengers including the polyphenols, prenylated flavonoids, stilbenes, and benzoic acid derivatives [5,9]. Phenolic acids and flavonols support the potential preventive health benefits of fruit-derived products' intake in relation to many diseases associated with oxidative stress [5,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the approach to new drugs through natural products has proved to be the single most successful strategy for the discovery of new drugs [2]. Mulberry leaf and fruit have been a part of traditional medicine for a long time and have been used to prevent or treat obesity, diabetes, and dyslipidemia [3]. It is a medicinally important plant belonging to genus Morus that is widely distributed in India, China, Japan, North Africa, Arabia, South Europe, etc.…”
Section: Introductionmentioning
confidence: 99%